Prolog programming for artificial intelligence - Bratko, Ivan (Addison-Wesley, 2012)
This best-selling guide to Prolog and Artificial Intelligence, which has been updated to include key developments in the field, concentrates on the art of using the basic mechanisms of Prolog to solve interesting AI problems.